2023
DOI: 10.3892/or.2023.8497
|View full text |Cite
|
Sign up to set email alerts
|

LAPTM5 regulated by FOXP3 promotes the malignant phenotypes of breast cancer through activating the Wnt/β‑catenin pathway

Abstract: Breast cancer remains the most common malignancy and the leading cause of cancer-associated mortality in women worldwide. Lysosomal protein transmembrane 5 (LAPTM5), a lysosomal membrane protein, plays an important role in several human malignancies. However, the biological functions and mechanism of LAPTM5 in breast cancer remain unclear. In the present study, the potential tumor-promoting effect of LAPTM5 was predicted by bioinformatics analysis. LAPTM5 was highly expressed in breast cancer clinical specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Accumulating evidence has revealed that the dysregulation of the Wnt/ β -catenin signal pathway contributes to the development and progression of several solid tumors and hematological malignancies ( Di Bartolomeo et al, 2023 ; Han et al, 2023 ; Li et al, 2022 ; Muto et al, 2023 ). In this study, we discovered that the Wnt/ β -catenin signal pathway was also abnormally expressed in ccRCC, suggesting the involvement of Wnt/ β -catenin in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has revealed that the dysregulation of the Wnt/ β -catenin signal pathway contributes to the development and progression of several solid tumors and hematological malignancies ( Di Bartolomeo et al, 2023 ; Han et al, 2023 ; Li et al, 2022 ; Muto et al, 2023 ). In this study, we discovered that the Wnt/ β -catenin signal pathway was also abnormally expressed in ccRCC, suggesting the involvement of Wnt/ β -catenin in ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expressions of lysosomal membrane proteins and cysteine cathepsins are associated with the upregulation of EMT marker proteins, induction of mesenchymal phenotype, and treatment resistance [ 281 , 282 , 283 , 284 , 285 ]. Induction of EMT is often regulated by TGF-β signaling, and inhibition of cysteine cathepsins can reverse this process and attenuate invasive growth [ 284 , 286 , 287 ].…”
Section: Lysosomal Involvement In Cancermentioning
confidence: 99%
“…LAPTM5 is a transmembrane receptor that localizes to intracellular vesicles and endosomes/lysosomes and transports proteins to lysosomes for degradation 9,10 . LAPTM5 acts as an oncogene and promotes malignant phenotypes, including metastatic potential, proliferation, and resistance to treatment 11,12 .…”
Section: Introductionmentioning
confidence: 99%